Influence of power factor enhancement on the thermoelectric figure of merit in Mg2Si0.4Sn0.6 based materials. Issue 6 (21st May 2014) - Dasgupta, T.; Stiewe, C.; de Boor, J.; Müller, E.
<x xml:space="preserve">Abstract</x> The influence of power factor enhancement on the superior thermoelectric (TE) performance of Mg2(Si, Sn) is studied based on a comparison with Mg2Si. Doped compounds with compositions of Mg2(Si0.4Sn0.6) are synthesized and the TE properties measured between room temperature and 773 K. Carrier concentration and hall mobilities at room temperature are measured on selected samples. Enhancement of the density‐of‐states effective mass and mobilities comparable to Mg2Si indicate band convergence in the solid solutions to be the cause of the power factor enhancement. Microstructural analysis shows the presence of secondary Si rich phases while the matrix corresponds to Mg2(Si0.3Sn0.7). A doped compound with this composition is synthesized and exhibits superior ZT values (compared to the Mg2(Si0.4Sn0.6) specimens) with a ZTmax ∼1.3 at 773 K.